ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ATAS PENGGELAPAN PAJAK - Gracia Emanuella Valentina, Amelia Sandra (Jurnal Akuntansi, 2019)
Tax is one of the main sources of income and expenditure for the nation of Indonesia. Therefore, every year the Government of Indonesia always tries to increase the amount of tax revenue. However, what happens is there are still some Taxpayers who seek to reduce the amount of tax payable by tax evasion. Tax evasion is an attempt to lighten the tax burden by violating existing laws. Meanwhile, this study aims to determine whether the factors such as equity, Self Assessment System, and service of the tax authorities affect the taxpayer's perception of tax evasion. The data obtained came from a questionnaire filled by 100 Individual Taxpayers Entrepreneurs in the field of Micro, Small and Medium Enterprises in the area of Kelapa Gading. The sampling technique used is Purposive Sampling, while the data analysis technique consists of descriptive statistics, data quality test, classical assumption test, hypothesis test, and multiple linear regression model analysis. The result of this research indicate that equity and service of the tax authorities influence to taxpayer perception on tax evasion, while Self Assessment System has no effect to taxpayer perception on tax evasionKeywords: Equity, Self Assessment System, Service of The Tax Authorities, and Tax Evasion